Analysis of HF propagation reception at ZS1HMO beacon receiver station - Mudzingwa, Courage (2016)
In this paper a sample High frequency (HF) beacon measurements that are part of the larger archive that is being collected at the beacon monitoring station in Hermanus, South Africa, ZS1HMO (34.42oS, 19.22oE) are presented. Using the NCDXF/IARU International Beacon Project, beacon signal observations from Africa, Asia, Australia, Europe, North America and South America wereanalysed. The observationsshow the variation in signal strength received at ZS1HMO from the six continents considered at each beacon frequency (14.10, 18.11, 21.15, 24.93 and 28.20 MHz). With the aid of HF propagation prediction software, ICEPAC, the predicted signal to noise ratio (SNR) values were compared with beacon SNR measurements gathered by the ZS1HMO monitoring stationfor a regional HF link, Ruaraka to Hermanus